1982
DOI: 10.1038/298347a0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and assembly of hepatitis B virus surface antigen particles in yeast

Abstract: The surface antigens of hepatitis B virus (HBsAg) has been synthesized in the yeast Saccharomyces cerevisiae by using an expression vector that employs the 5'-flanking region of yeast alcohol dehydrogenase I as a promotor to transcribe surface antigen coding sequences. The protein synthesized in yeast is assembled into particles having properties similar to the 22-nm particles secreted by human cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
307
0
9

Year Published

1984
1984
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(321 citation statements)
references
References 28 publications
5
307
0
9
Order By: Relevance
“…However, under normal physiological conditions, most proteins are present in low cellular concentrations and cannot be purified out of the tissue itself. Since the early eighties it is has been possible to express proteins recombinantly in heterologous host cells like the bacterium Escherichia coli (E.coli) [11,12] or the yeast Saccharomyces cerevisiae (S.cerevisiae) [13]. These host cells can produce a large amount of recombinant protein, that enables the characterization of proteins with a low cellular abundance.…”
Section: Introductionmentioning
confidence: 99%
“…However, under normal physiological conditions, most proteins are present in low cellular concentrations and cannot be purified out of the tissue itself. Since the early eighties it is has been possible to express proteins recombinantly in heterologous host cells like the bacterium Escherichia coli (E.coli) [11,12] or the yeast Saccharomyces cerevisiae (S.cerevisiae) [13]. These host cells can produce a large amount of recombinant protein, that enables the characterization of proteins with a low cellular abundance.…”
Section: Introductionmentioning
confidence: 99%
“…3A). From the results obtained from the immunological analysis and from the measurements of the refraction indices it can be concluded that the proteins P fsl6 -S and HBsAg assemble into 22-nm particles (P fsl6 -S,S) and as efficient as native HBsAg [25].…”
Section: Identification O F Recombinant Proteins Synthe Sized In Yeastmentioning
confidence: 99%
“…HBsAg synthesized in yeast is accumulated in particles similar in size as the 2 2 -nm particles found in human sera after hepatitis B infection which have a buoyant density of 1.18 g cm " 3 [25]. To study whether the recombinant P fsl6 -S fusion proteins and HBsAg synthesized in yeast Y1655 also accumulate in 22 nm particles, crude extracts of Y1655 yeast cells were subjected to CsCl equilibration centrifuga tion as described [24].…”
Section: Characterization O F Yeast Particles Containing Recombinant mentioning
confidence: 99%
“…Chiron, près de Berkeley dans la baie de San Francisco, aété la premièreà réussir. L'expression recombinante de l'antigène de surface de l'hépatite B chez la levure permit la production de particules membranaires semblablesà celles du virus, qui se sont révélées hautement immunogènes, et qui ontété commercialisées comme un vaccin très efficace contre l'hépatite, seule source aujourd'hui de ce produit (Valenzuela et al, 1982). L'hépatite Bétant la cause majeure du cancer primitif du foie, l'introduction réussie de cette préparation issue de la voie de sécrétion de la levure pourrait, si elleétait diffusée très largement, réduire de manière dramatique l'incidence du cancer du foie.…”
Section: Les Mutants De Sécrétionunclassified